THE FUNCTION OF MEMORY AND HISTORY IN POSTCOLONIAL LITERATURE - Ne`matova Dilshoda Xurmatillo qizi; Abdurakhmanova Diana Valerevna (TADQIQOTLAR.UZ, 2024)
Abstract: This article explores how postcolonial writers use memory to resist colonial erasures and affirm cultural heritage, while also addressing the lasting psychological and societal impacts of colonial rule. By examining works such as Things Fall Apart by Chinua Achebe, Midnight’s Children by Salman Rushdie, and Wide Sargasso Sea by Jean Rhys, the essay highlights how memory and history intersect to challenge dominant colonial narratives and assert alternative perspectives. It further discusses the intergenerational transmission of memory and its role in shaping collective identities, as well as the potential for memory to facilitate reconciliation and healing in postcolonial societies. Ultimately, memory and history emerge as indispensable elements in postcolonial literature, offering pathways for resistance, understanding, and renewal in the aftermath of colonization.